Sensory Futures : Deafness and Cochlear Implant Infrastructures in India - Friedner, Michele Ilana, 1978- (Book collections on Project MUSE., 2022)
"Sensory Futures explores deaf people's desires to create habitable worlds, grappling with their futures amid a surge in biotechnical interventions and disability rights activism. With implications for a broad range of disability experiences, this sensitive, in-depth research focuses on the specific experiences of deaf people, both children and adults, and the structural, political, and social possibilities biotechnological and social "cures" offer"--